Erratum to: Search for PeVatrons at the Galactic Center using a radio air-shower array at the South Pole - A. Balagopal V.; A. Haungs; T. Huege; F. G. Schröder (European Physical Journal C: Particles and Fields, 2018)
The original article contains typographic errors in the appendix B, which deals with the process of generating a noise trace.